2014
DOI: 10.1111/bjd.12954
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for mycosis fungoides: critical commentary on a Cochrane Systematic Review

Abstract: This review of RCTs for MF interventions led to more questions than answers due to a dearth of adequately powered RCTs. Only one meta-analysis could be performed. The remaining review was based on single trials, many of which assessed infrequently used treatments or regimens and are not reflective of current clinical practices. Only two of the 14 RCTs assessed patient health-related quality-of-life outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 70 publications
(124 reference statements)
0
5
0
Order By: Relevance
“…This conflicting data generated over decades portrait the basic dilemma of lymphoma research: the lack of comparable trials, reliable systematic reviews, or meta‐analyses . Nevertheless, despite the relatively low number of patients in our study, our results are in conjunction with the existing works, although different modes of psoralen application were used.…”
Section: Discussionmentioning
confidence: 62%
“…This conflicting data generated over decades portrait the basic dilemma of lymphoma research: the lack of comparable trials, reliable systematic reviews, or meta‐analyses . Nevertheless, despite the relatively low number of patients in our study, our results are in conjunction with the existing works, although different modes of psoralen application were used.…”
Section: Discussionmentioning
confidence: 62%
“…Refractory cases with multiple tumor lesions or transformed or erythrodermic MF may require systemic treatment. Some of the systemic treatments available include: interferon α associated with PUVA; systemic retinoids, such as bexarotene; methotrexate; pralatrexate; monochemotherapy with chlorambucil, associated with prednisone; liposomal doxorubicin; and, in refractory cases, systemic polychemotherapy with gemcitabine and vinorelbine, and anthracycline-based schemes 29,30 . Studies with allogeneic bone marrow transplantation have shown excellent responses, with long periods of remission 31 .…”
Section: Classical Mfmentioning
confidence: 99%
“…Firstly, we want to thank Wu et al 1 for their clear and very considerate evaluation of our Cochrane Systematic Review. 2 We fully support their notion for sufficiently powered randomized controlled trials (RCTs) aiming at improving not only survival but also patient-reported outcomes such as quality of life.…”
Section: Response To 'Interventions For Mycosis Fungoides: Critical Cmentioning
confidence: 99%
“…Firstly, we want to thank Wu et al . for their clear and very considerate evaluation of our Cochrane Systematic Review .…”
mentioning
confidence: 99%